Relatório de Estágio Profissional "Uma caminhada na luz do saber - A partilha do passado, um sentido no presente, um amanhã construído" - Joana Daniela Silva Fernandes (2017)
The year of Internship is an integral and unquestionable part of the training process of the students and is reflected in a year of implementation and the report is a testimony of the experiences and a source of support and reflection on them. Implemented in a public School, in a nucleus made up of three elements, my pedagogical practice was centered under the teaching of three classes: two 9th years and a fifth year, as well as under the supervision of a group direction and a sports team school. In the construction of this internship report I tried to portray my most outstanding experiences that led me to the configuration of my professional identity. I structured it in five chapters, where it has a narrative in the description of the main episodes of this year of formation and development. Yet it is divided into three dimensions. A more personal and descriptive of the context of the stage, another more concrete, where my adventures and challenges of pedagogical practice are mirrored, from which I highlight the routines and the control of the class, the instruction and feedback. And finally, a part that wants to demonstrate the importance of involvement in the school community. As a complement, a research study emerges that has allowed me to clarify doubts that have arisen during the monitoring of school sports. The internship report aims to show the growth, evolution and experience of a student-trainee through the reporting of an identity that now appears more conscious, more critical, more responsible, more autonomous and above all, more reflective of someone who wanted, more than anything, to be a physical education teacher.